Identification and analysis of risk factors in the process of receiving goods into the warehouse - Ewa Kulińska; Julia Giera (Foundations of Management, 2019)
The process of receiving goods into the warehouse is the first stage of warehouse manage-ment. Correct receipt of fast-moving goods is the key element of the storage process as well as of the entire supply chain, which is why it is so important to avoid any disruptions at this stage. In order to identify and analyze the associated risk factors, two quality risk management methods were applied: a risk map and the fast-moving consumer goods (FMCG) method, whose goal was to determine the magnitude of individual risk factors. The presented findings indicate which risk factors are the most hazardous to the goods receipt process. A correlation was found to exist for the value of goods as well as the continuity of the consequences entailed by the occurrence of a specific factor. The article pre-sents preventive mechanisms as a risk management tool.
Keywords: B40; D22; D30; 650; warehouse management; goods receipt process; risk